Implementasi Model Goal Programming untuk Menganalisis Kinerja Keuangan Perusahaan - Novianingsih, Khusnul; Marsyanda, Meifa Putri; Kustiawan, Cece (Diophantine Journal of Mathematics and Its Applications, 2024)
Company financial reports can be used to analyze a company's financial performance. This research discusses financial performance analysis to determine the company's financial weaknesses and strengths. Using the analysis results, the company can be determined financial policies for the next period, so the company can achieve the optimal financial performance. The financial performing model can be modelled as a multi-objective problem. The model is solved by converting the multi-objective model into a goal programming model. Then, it is solved using the Modified Simplex Method. We implemented the model to analyze the financial report of a big company. The results show that the company has a good financial performance.